Comparison of macaque and human L- and M-cone driven electroretinograms - Kremers, Jan; Aher, Avinash; Parry, Neil R.A.; Patel, Nimesh B.; Frishman, Laura J. (Experimental Eye Research, 2021)
Purpose: The macaque retina is often used as a model for the human retina. However, there are only a handful of direct in vivo comparisons of the retinal physiology in humans and macaques. In the current study, ERG responses to luminance, L-cone isolating and M-cone isolating stimuli with sinusoidal, sawtooth and square wave temporal profiles were measured. The results were compared with those obtained from human observers. Methods: The responses from five anesthetized adult macaques were measured. Full field stimuli were created. L- and M-cone isolating stimuli were based on the triple silent substitution technique. Sinusoidal stimuli had temporal frequencies between 4 and 56 Hz in 4 Hz steps. Sawtooth stimuli with rapid-on ramp-off and with rapid-off ramp-on excitation profiles had a frequency of 4 Hz. Square stimuli were presented at 2 Hz. Results: Macaque and human ERGs in response to L- and M-cone isolating stimuli reflect L/M opponency and luminance activity. In responses to sine waves, cone opponency dominates at low temporal frequencies (4–12 Hz); luminance dominates at high temporal frequencies. The responses to sawtooth and square wave stimuli reflect a mixture of chromatic and luminance activity. L:M response ratios vary between individuals both in macaques and humans. Macaques show more complex responses, including greater second harmonic contributions than those in humans. Conclusions: Macaque and human ERGs share basic underlying mechanisms reflecting L/M opponency and luminance activity. There may be quantitative differences possibly reflecting differences in contributions of inner retinal mechanisms to the ERGs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Cone opponency; Electroretinogram; Human; L-cones; Luminance; M-cones; Macaque